2020
DOI: 10.1159/000508699
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Innate and Adaptive Immunological Characteristics in Patients with IgG4-Related Disease

Abstract: Background: Immunoglobulin G4-related disease (IgG4-RD) is a systemic immunological disorder characterized by fibroinflammatory conditions; however, the pathobiology of IgG4-RD has not been fully identified. Objective: This study aimed to analyze systemic differences of innate and adaptive immune cells from healthy controls and patients with IgG4-RD. Methods: Healthy controls (n = 9) and IgG4-RD patients (n = 7) were recruited with informed consent. Peripheral blood was collected from healthy controls and IgG4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…These subsets include CD14 + monocytes (MNs) (LYZ + CD14 + ), CD16 + MNs (LYZ + FCGR3A + ), DCs (CD1C + ), CD4 + T cells (CD4 + ), CD8 + T cells (CD8A + ), proliferating lymphocytes (MKI67 + ), natural killer (NK) cells (KLRF1 + ), B cells (CD19 + ), and platelets (PPBP + ) (Figure 1E). Of note, the percentages of B cells and CD4 + T cells tended to be lower in IgG4-RD patients than in HCs, while CD14 + MNs showed an opposite trend (Figure 1, F and G), which was also demonstrated in a recent study (14).…”
Section: Resultssupporting
confidence: 83%
“…These subsets include CD14 + monocytes (MNs) (LYZ + CD14 + ), CD16 + MNs (LYZ + FCGR3A + ), DCs (CD1C + ), CD4 + T cells (CD4 + ), CD8 + T cells (CD8A + ), proliferating lymphocytes (MKI67 + ), natural killer (NK) cells (KLRF1 + ), B cells (CD19 + ), and platelets (PPBP + ) (Figure 1E). Of note, the percentages of B cells and CD4 + T cells tended to be lower in IgG4-RD patients than in HCs, while CD14 + MNs showed an opposite trend (Figure 1, F and G), which was also demonstrated in a recent study (14).…”
Section: Resultssupporting
confidence: 83%
“…(2) CD4 + + Tfh in IgG4-RD . Generally, in IgG4-RD, these cells are significantly increased in both peripheral blood and disease-affected organs [ 6 , 9 , 29 , 60 , 66 , 67 , 70 ].…”
Section: Igg4-related Diseases (Igg4-rd)mentioning
confidence: 99%
“…Grados et al showed that CD4 + CXCR5 + PD1 + Tfh cells were normalized under RTX treatment [ 71 ]. However, Sohan et al revealed that, after RTX treatment, Tfh cells and TGF- β -producing cells remained in the blood of IgG4-RD patients, suggesting that these cells might be risk factors for incomplete resolution of the inflammatory process [ 9 ].…”
Section: Igg4-related Diseases (Igg4-rd)mentioning
confidence: 99%